Type player 3 - Sandu Cultural Media (Guangzhou : Sandu Cultural Media, 2014)
Type Player 3 displays the best of types, demonstrating how designers dont just design type, but turn it into a subject of play with letters that go beyond the page to capture the unique needs and aesthetic preferences of designers and brands. The words and letters within exist as physical objects that embody the messages they spell out in their very design - items of clothing demonstrate exactly what it means to be "colourful". Essential for anyone looking for provocative new ways to get their message across and the perfect follow up to Type Player 2 (2012).
boek